Trends, gaps, and research prospects of the convergence of immersive technology and AI in physics learning: a bibliometric study. - Vandan Wiliyanti; Siti Sarah; Viyanti Viyanti (Program Studi Pendidikan Fisika FKIP Universitas Muslim Maros, 2026)
The convergence of immersive technology and artificial intelligence (AI) is transforming physics learning into a more interactive and adaptive environment. However, research on this topic has not been systematically mapped. This study analyzes research trends, gaps, and future prospects using a bibliometric approach. Data were collected from the Scopus database covering publications from 2020 to 2026. Following the screening process, 100 articles were analyzed using Bibliometrix-Biblioshiny. The analysis included publication trends, collaboration networks, keyword co-occurrence, thematic mapping, and conceptual structure. The results revealed a substantial increase in publications, with artificial intelligence, virtual reality, immersive technologies, and STEM education emerging as dominant themes. The United States, China, and Indonesia were the leading contributors. The findings indicate considerable opportunities for future research, particularly in adaptive learning and immersive learning environments for physics education. This study provides a scientific overview that may serve as a reference for future research on the convergence of AI and immersive technology in physics learning.